Early stages of the enigmatic Prodidactis mystica (Meyrick) with comments on its new family assignment (Lepidoptera: Prodidactidae) - Epstein, Marc E.; Brown, John W. (Zootaxa, 2003)
Prodidactis Meyrick is a monotypic genus restricted to southern Africa (South Africa, Zimbabwe, and Swaziland). The early stages of P. mystica (Meyrick) are described and illustrated for the first time; the larval host is Nuxia congesta (Loganiaceae). The genus previously has been assigned to Tortricidae, Yponomeutidae, and Limacodidae; however, an examination of larval, pupal, and adult characters contradict these placements. Although evidence from the larval stage places Prodidactis in Crambidae (Pyraloidea), features of the adults convincingly contradict this assignment. As an interim solution, we propose Prodidactidae, new family, to accommodate this unusual genus.